Pros of AI in higher education: artificial intelligence (AI) improved learning outcomes - Kechil, Rafizah; Wan Mohammad, Wan Anisha (Unit Penerbitan Dan Publisiti JSKM, 2025)
As artificial intelligence (AI) permeates the educational landscape, it brings with it a host of benefits that contribute to improved learning outcomes and streamlined administrative processes in higher education institutions. Below, we explore some of the significant advantages of AI implementation in universities, encompassing personalized learning experiences, enhanced administrative efficiency, improved resource access, and heightened student engagement. Personalized Learning Experiences One of the standout contributions of AI in higher education is its ability to provide tailored learning experiences. This personalization enhances student engagement and outcomes, leading to a more effective learning environment. Examples of how AI achieves this include: • Adaptive Learning Systems: These platforms utilize data analytics to assess a student’s current knowledge, skills, and learning pace. For instance, platforms like Smart Sparrow and DreamBox Learning adjust the curriculum dynamically, offering customized resources that align with the learner’s needs. Studies indicate that personalized instruction can lead to higher retention rates and better academic performance compared to traditional, one-size-fits-all approaches.